DIGLOSSIA PHENOMENON OF MADURESE INTERACTION AT ISLAMIC BOARDING SCHOOL NAHDLATUL TOLIBIN IN BLADO WETAN-BANYUANYARPROBOLINGGO - Nurin Febriati Nabilah; Sri Andayani (JURNAL LITERASI, 2022)
This study is of diglossia have to explain the varieties of Madurese language used at Islamic boarding school Nahdlatul Tolibin. The reason of choosing the Madurese language that located in Nahdlatul Tolibin is because there was Madurese diglossia phenomenon in Islamic boarding school “Nahdlatul Tolibin”. This study applies sociolinguistics as the theoretical approach which taking diglossia as the theory of it. The research design of this study is qualitative descriptive method. The observation and interviewing method becomes the data collection. The observation is continued with third technique “recording technique” and the continuous forth technique “writing technique”, however interviewing method continuous third and fourth techniques “recording and writing techniques”. In analyzing the data, the researcher uses Spradley method for the data analysis, they are: Domain analysis, 2) Taxonomy analysis. The data validity examination method is used the data triangulation because the researcher uses several kinds of data sources and proof of different situation, then the data analysis description method is applying the formal and informal.